Incidence and survival of dementia in a general population of Japanese elderly: the Hisayama study. Issue 4 (31st October 2008) - Matsui, Y; Tanizaki, Y; Arima, H; Yonemoto, K; Doi, Y; Ninomiya, T; Sasaki, K; Iida, M; Iwaki, T; Kanba, S; Kiyohara, Y
Abstract : Objective: To estimate the incidence and survival rates of total and cause specific dementia in a general Japanese population. Methods: A total of 828 subjects without dementia, aged 65 years or over, were followed-up prospectively for 17 years. Dementia was subdivided into cause specific subtypes: namely, Alzheimer's disease (AD), vascular dementia (VD), dementia with Lewy bodies (DLB), combined dementia and other types of dementia. During the follow-up, 275 subjects developed dementia; of these, 251 (91.2%) were evaluated morphologically, with 164 subjected to brain autopsy examination and the remaining 87 to neuroimaging. Results: The incidences of total dementia, AD, VD, DLB, combined dementia and other types of dementia were 32.3 (n = 275), 14.6 (124), 9.5 (81), 1.4 (12), 3.8 (33), and 3.1 (16) per 1000 person years, respectively. The incidences of AD, combined dementia and other types of dementia rose with increasing age, particularly after the age of 85 years, but this tendency was not observed for VD or DLB. The survival curve of dementia cases aged 65–89 years was significantly lower than that of age and sex matched controls (10 year survival rate, 13.6% vs 29.3%; hazard ratio 1.67; 95% confidence interval 1.31 to 2.13). The 10 year survival rates were not significantly different among dementia subtypes. Conclusions: Our findings suggest that the Japanese elderly population has a high risk for the development of dementia, specifically AD and VD, and once dementia is established, the risk of death is considerable.